TRANSLATION METHODS OF THE SONG "SPEECHLESS" INTO THE INDONESIAN VERSION "BUNGKAM" FROM THE SOUNDTRACK OF THE ALADDIN MOVIE - Sood, Azzharah Kautsar; Baharuddin, Baharuddin; arafiq, Arafiq (JOURNAL OF LANGUAGE, 2024)
This study explores the translation of the song "Speechless" from Disney's Aladdin into the Indonesian version "Bungkam." Song translation is essential in connecting diverse cultures and allowing audiences to experience music in their native languages. It involves more than just converting words; it requires understanding cultural nuances and emotional depth. The research focuses on the methods used by translator Asmi Nurais, applying Peter Newmark's translation theories as a framework. The findings reveal that significant changes in imagery and phrasing reflect cultural adaptation, making the song more relatable to Indonesian listeners. Nurais employed a Free Translation method, prioritizing the song's themes of empowerment and emotional expression over strict adherence to the original lyrics. This approach ensures that the essence of the song is preserved while making it accessible to a new audience. This study contributes to the field of musical translation studies by highlighting the complexities involved in adapting lyrics for different cultural contexts. It emphasizes the role of translators as cultural mediators who navigate between languages and meanings. By showcasing the balance between fidelity to the source material and the need for cultural relevance, this research enriches our understanding of song translation. Ultimately, it underscores the importance of creative adaptation in making music resonate across borders, fostering emotional connections among listeners from different backgrounds.